Bed nucleus of the stria terminalis GABA neurons are necessary for changes in foraging behaviour following an innate threat - Ly, Annie; Barker, Alexandra; Hotchkiss, Hayden; Prévost, Emily D.; McGovern, Dillon J.; Kilpatrick, Zachary; Root, David H. (The European journal of neuroscience, 2023)
Foraging is a universal behaviour that has co‐evolved with predation pressure. We investigated the role of the bed nucleus of the stria terminalis (BNST) GABA neurons in robotic and live predator threat processing and their consequences in post‐threat encounter foraging. Both robotic and live predator interactions increased BNST GABA neuron activity. Mice were trained to procure food in a laboratory‐based foraging apparatus in which food pellets were placed at incrementally greater distances from a nest zone. After mice learned to forage, they were exposed to a robotic or live predator threat, while BNST GABA neurons were chemogenetically inhibited. Post‐robotic threat encounter, mice spent more time in the nest zone, but other foraging parameters were unchanged compared with pre‐encounter behaviour. Inhibition of BNST GABA neurons had no effect on foraging behaviour post‐robotic threat encounter. Following live predator exposure, control mice spent significantly more time in the nest zone, increased their latency to successfully forage, and significantly altered their overall foraging performance. Inhibition of BNST GABA neurons during live predator exposure prevented changes in foraging behaviour from developing after a live predator threat. BNST GABA neuron inhibition did not alter foraging behaviour during robotic or live predator threats. We conclude that these results demonstrate that while both robotic and live predator encounters effectively intrude on foraging behaviour, the perceived risk and behavioural consequences of the threat are distinguishable. Additionally, BNST GABA neurons may play a role in the integration of prior innate predator threat experience that results in hypervigilance during post‐encounter foraging behaviour.